Effect of early intervention for early-stage psychotic disorders on suicidal behaviours – a systematic review protocol - Tahmazov, Elkhan; Blachier, Athéna; Nabbe, Patrice; Guillou-Landreat, Morgane; Walter, Michel; Lemey, Christophe (Frontiers in Psychiatry, 2024)
Background The early stages of psychotic disorders correspond to the early phases of the disease and include the prodromal phase and first-episode psychosis; they constitute a period at high risk of suicidal behaviour. A long duration of untreated psychosis (DUP) is among the risk factors of suicidal behaviour identified in this early period. Many studies have shown the effectiveness of early interventions on the overall prognosis of psychotic disorders in the early stages, and early intervention strategies have been developed and tested worldwide. Several authors reported an improvement in suicidal behaviours; however, all these data have not been systematically analysed yet. The main objective of this systematic review was to collect evidence on the effect on suicidal behaviour of early interventions for patients in the early stages of psychotic disorders. Methods We will carry out a systematic review of the literature according to the PRISMA criteria by searching articles in five databases (PubMed, Cochrane, PsycINFO, Scopus, EMBASE), without restriction on the publication date. The selection criteria are: articles (any type; e.g. prospective, retrospective, controlled or uncontrolled, and literature reviews) on early interventions for psychotic disorders in the early stages with data on suicide attempts, death by suicide, suicidal ideation; articles written in English or French. Exclusion criteria are: articles on suicidal behaviours in patients with psychotic disorders in the early stages, but without early intervention, and articles on early-stage psychotic disorders without data on suicidal behaviours. Discussion If this review confirms the effectiveness on suicidal behaviours of early interventions for young patients with psychotic disorders, the development/implementation of such intervention programmes should be better promoted. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier CRD42021237833.